Scoping Out Elements of Sociocultural Adaptation in European Urban Agriculture - Cavicchi, Bianca; Hegnes, Atle Wehn (Frontiers in Sustainable Food Systems, 2021)
This paper explores and sheds light on the elements, complexity, and dynamics of socio-cultural adaptation to climate change in European Urban Agriculture (EU UA). We use a scoping-exploratory review to search and unveil elements of socio-cultural adaptation (SCA) in the existing literature on European urban agriculture. We categorize these elements into three main categories. This categorization can inform and be further explored, operationalized, and developed in new case-study-based research and serve as a starting point to better understand social adaptation to climate change in urban contexts, and beyond. Key results draw attention to a) socio-technical and socio-ecological innovations as critical to socio-cultural adaptation to climate change b) some elements of SCA identified through the scoping review seem more central than others for the adaption process c) we are left with the question of whether we need to bridge social science with biology sciences, such as human behavioural biology and neurobiology to find the answer to deeper questions about SCA.